HYDRAULIC PERFORMANCE OF TRICKLE IRRIGATION EMITTERS UNDER FIELD CONDITION - Nazeer, M. (The Nucleus, 2010)
The efficiency of trickle irrigation system depends on the uniform distribution of water through mechanical device, the emitter. The aim of this research study was to compare and evaluate the hydraulic performance of pressurecompensating and non pressure-compensating emitters under field condition. Both types of emitters were subjected to different operating pressures (50,100,150,200 and 250KPa) of the water source. Three hydraulic performance parameters including manufacturer’s coefficient of variation, hydraulic design’s coefficient of variation and total coefficient of variation were tested for pressure-compensating and non pressure-compensating emitters. Manufacturer’s coefficient of variation (CVM) values was compared with test results for both types of emitters. Hydraulic design’s and total coefficients of variations were also determined at field level. The results showed that pressurecompensating emitters has less dependency on operating pressure as compared to non pressure-compensating ones which was further clarified trough statistical analysis by their linearity at 95% confidence and prediction intervals